Ottoman Wikālas in Cairo: Islamic Architecture Beyond the Mosque - Moussa, Yumna (AUC Knowledge Fountain, 2026)
This thesis traces one of the largest architectural typologies in Cairo: the wikāla, a type of urban caravanserai unique to Egypt. Estimated to have reached more than five hundred buildings by the 18th century, the wikāla was the building of choice for most patrons in Ottoman Cairo. This study initially investigates the evolution of commercial architecture within the Islamic city. It then explores the defining architectural features of Cairene wikālas built between the 16th and 18th centuries—their plans, decorative/iconographic programs, and urban distribution—based on waqfiyyas, chronicles, travelers’ accounts, and photographic archives. Since many of these buildings are no longer extant and have not been fully documented in previous studies, a catalogue of Ottoman wikālas in Cairo, including unlisted buildings, was compiled as part of this study. By reconstructing Ottoman wikālas within their historical context, this thesis raises several questions about the methodological approaches associated with the study of Islamic architecture. It reassesses the validity of the mosque-centered framework for evaluating stylistic evolution by emphasizing the shifting patterns of patronage that accompanied Ottoman rule. Moreover, this study argues that the architectural waqfs of Ottoman Cairo were much larger than previously assumed, and were accompanied by an intentional building program and urbanization scheme. Finally, the thesis highlights the major role wikālas played in Ottoman Cairo’s scholarly milieu, serving as non-Sunni madrasas, spaces of manuscript production, and academic extensions of al-Azhar. This demonstrates that commercial space was closely tied to religious practice in the Islamic city.